On controversial issues of systemic toxicity of local anesthetics - R. E. Lakhin (Вестник анестезиологии и реаниматологии, 2020)
The letter draws attention to the provisions on the use of fat emulsion when systemic toxicity of local anesthetics develops that was published in the article titled Disputed Issues of Systemic Toxicity of Local Anesthetics. (Messenger of Anesthesiology and Resuscitation, no. 1, 2020). It is noted that the use of fat emulsion when systemic toxicity of local anesthetics develops is a method of therapy accepted worldwide and included in the protocols of cardiopulmonary resuscitation.